Forward and back is not enough: applying best practices for translation of pediatric sleep questionnaires - Thompson, Darcy A.; Fineman, Melissa S.; Miramontes Valdes, Estefania; Tschann, Jeanne M.; Meltzer, Lisa J. (Frontiers in Sleep, 2024)
Cultural differences in the experience of sleep warrant consideration in the measurement of sleep across populations. This requires careful attention to both language and culture when translating survey measures. While forward and back translation is the most commonly used approach, it has numerous limitations if used as an isolated method. Best practice guidelines recommend a multi-step team-based approach for translating questionnaires. We present our recent experience applying best practices in a study with both Spanish and English-speaking Mexican American mothers of toddlers. This work is part of a larger project that will measure parental sleep-related beliefs and parenting practices in Mexican American parents of toddlers. We utilized a team-based approach to translation and cultural adaptation, assembling a diverse, bilingual, and bicultural team. The translation process started with items and measures that we had selected, revised as needed, or created. New items were based on constructs identified in semi-structured interviews and focus groups used to explore parental sleep-related beliefs and parenting practices in the target population. Following this, our translation process included forward and back translation, harmonization and decentering, cognitive interviewing, debriefing, adjudication, and proofreading. We outline details of our process and the rationale for each step. We also highlight how each step contributes to ensuring culturally appropriate items with conceptual equivalence across languages. To ensure inclusivity and scientific rigor within the field of sleep research, investigators must utilize best practices for translations and cultural adaptations, building on the foundation of cultural constructs often identified in qualitative work.